THE ROLE OF MATHEMATICS ANXIETY IN COURSE PREFERENCE: A QUANTITATIVE STUDY OF PROSPECTIVE UNDERGRADUATES IN ENUGU STATE, NIGERIA - Okon, Ndubuisi U. (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2022)
The present study examined course preference among prospective undergraduates based on mathematics anxiety. One hundred and thirty-eight post-secondary school students participated in the study. The Maths Anxiety Scale (MAS) was used to measure the respondent's level of math anxiety. Their subject choice was indicated in the demographic section. A linear regression analysis was conducted to examine the predictive effect of mathematic anxiety on the prospective student's course preference. The study showed that mathematic anxiety statistically significantly predicted the respondent's course preference F (1,136), 128.97, P<.000. Notably, the finding revealed that mathematics anxiety contributed to about 16.1% of the prospective undergraduate's course preference variation. Thus, the assumption that mathematic anxiety will significantly predict course preference among the prospective undergraduates was true. The findings and practical implications of the study are discussed.